Association of HLA mismatch with death with a functioning graft after kidney transplantation: a collaborative transplant study report - Opelz, Gerhard; Döhler, Bernd (American journal of transplantation, 2012)
In the current analysis, CTS data from more than 177 000 kidney transplant recipients were examined to investigate a possible relationship between HLA mismatches and the risk of DWFG overall and because of cardiovascular causes, infection or cancer.